KONTRIBUSI MOTIVASI BELAJAR DAN SUASANA BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN KETERAMPILAN KOMPUTER DAN PENGELOLAAN INFORMASI (KKPI) SISWA KELAS X TKJ SMKN 4 TAKENGON-ACEH TENGAH - Badrun Badrun; Efrizon Efrizon; Legiman Slamet (Universitas Negeri Padang, 2016)
This study was motivated by the problem of low learning outcomes in subjects Computer Skills and Information Management (KKPI) class X Computer Engineering and Networks in SMK Negeri 4 Takengon, where 30% of students get to learn the results below minimum completeness criteria (KKM). KKM assigned school on the subjects KKPI is 75 with a range of values of 0 - 100. The purpose of this study is to reveal the contribution of learning motivation and learning atmosphere on the results of study subjects Computer Skills and Information Management (KKPI) class X Computer Engineering and Networks SMKN 4 Takengon. This research is a correlation associative nature.The population in this study were all students of class X Computer Engineering and Networks SMKN 4 Takengon, consists of two classes of 40 people. A sampling technique that total sampling where the sample is whole members of the population because the subject is less than 100 persons. The data obtained from the student learning outcomes subject teachers Skills Computer and Information Management (KKPI) SMK Negeri 4 Takengon. While data on the motivation to learn and the learning environment are collected through a questionnaire using a Likert scale that have been tested for validity and reliability. File was analyzed using statistical methods with the help of software Microsoft Excel 2007.The result showed: (1) learning motivation accounted for 24.61% of the results of class X student of SMK Negeri 4 Takengon; (2) Atmosphere Learning accounted for 23.54% of the results of class X student of SMK Negeri 4 Takengon; (3) learning motivation and learning atmosphere together accounted for 47.90% of the results of class X student of SMK Negeri 4 Takengon. So it can be concluded that the motivation to learn and contribute to the learning atmosphere of learning outcomes, the higher the motivation to learn and the better learning environment, then it will get better learning results. Keywords : Motivation, Atmosphere Learning, Learning Outcomes, Associative correlation, Total Sampling.